Essential Readings in Magnesium Technology - Mathaudhu, Suveen; Luo, Alan.; Neelameggham, Neale; Nyberg, Eric.; Sillekens, Wim.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This is a compilation of the best papers in the history of Magnesium Technology, a definitive annual reference in the field of magnesium production and related light metals technologies. The volume contains a strong topical mix of application and fundamental research articles on magnesium technology. Section titles: 1.Magnesium Technology History and Overview 2.Electrolytic and Thermal Primary Production 3.Melting, Refining, Recycling, and Life-Cycle Analysis 4.Casting and Solidification 5.Alloy and Microstructural Design 6.Wrought Processing 7.Modeling and Simulation 8.Joining 9.Corrosion, Surface Treatment, and Coating.
Keywords: Metals; Coatings; Tribology; Corrosion and anti-corrosives.; Mechanical engineering; Metals and Alloys; Coatings; Tribology; Corrosion; Mechanical Engineering